PATHOGENESIS AND CLINICAL COURSE OF TYPE 2 DIABETES MELLITUS CONCOMITANT WITH OBESITY - Shaienko, Z.О.; Popruga, A.O.; Lihonenko, O.V. (World of Medicine and Biology, 2021)
The paper considers the role of obesity in the development of type 2 diabetes mellitus. Features of the conjoint pathogenesis are specified. Purpose: to study the features of the clinical course of type 2 diabetes mellitus concomitant with obesity on the basis of the comprehensive study of the indicators of systemic nonspecific inflammation, insulin resistance, carbohydrate and lipid metabolism. 268 patients with type 2 diabetes mellitus have been treated. The patients were randomized into 2 groups: type 2 diabetes mellitus without obesity and type 2 diabetes mellitus and obesity. The analysis of carbohydrate and lipid metabolism, biomarkers of inflammation and indicators that characterize insulin resistance in all patients with type 2 diabetes mellitus and obesity has found the significantly higher indicators in contrast to patients with diabetes without obesity. It is recommended to consider obesity as the basis for the adverse course of the type 2 diabetes mellitus concomitant with obesity and the onset and progression of complications.
Keywords: diabetes mellitus; visceral obesity; insulin resistance; chronic low-intensity inflammation